A Halal-Haram Studies: Food-Grade Lubricants in the Food Industry - Nurul Huda Fauzan Naufal Dian; Syah Sultan Ali Muzakhar; Fahmi Fahmi; Setiyo Gunawan (Halal Research, 2025)
Food-grade lubricants are important in the food industry because they maintain the efficiency and safety of the production process. Halal and haram aspects in Islam are essential in food-grade lubricants because of potential contamination of lubricants in food products. The halal or haram status of a lubricant is determined by the raw materials, manufacturing process, and potential contamination of food-grade lubricants. Some food-grade lubricants use animal-derived raw materials such as stearic acid. The primary source of raw lubricant material is the animals used. The use of prohibited animals will change the status of lubricants to haram. In addition to raw materials, lubricant production can use non halal materials such as alcohols and catalysts. If the catalyst and alcohol used are not in accordance with SNI 99004-2021, then food-grade lubricants cannot be halalised. Lubricants can also be contaminated by L. monocytogenes. The infections caused by these bacteria are health hazards, especially for humans with weakened immunity. This potential surely causes harm to humans and can affect the halal status of lubricants. Due to the critical need for halal lubricants, the oil and gas company PT Pertamina has initiated the existence of five halal-certified lubricants in Indonesia: FG-GO 150, FG-GO 220, FG-GO 320, FG-GO 460, and FG-HO 46.